IMPACT OF SOCIAL MEDIA MARKETING STRATEGIES ON CONSUMER FAST-FOOD PURCHASE DECISIONS: AN EXTENSIVE REVIEW - Prof. Himanshu Sharma1; Dr. Akhilesh Pandey2 (Utilitas Mathematica, 2025)
The fast-food industry is undergoing a major transformation driven by the strategic use of social media, which is reshaping consumer behavior and purchasing patterns. This comprehensive review examines how social media strategies influence fast-food consumption by leveraging platforms such as Instagram, Facebook, Twitter, TikTok, and YouTube. The paper explores how brands integrate interactive campaigns, influencer marketing, and user-generated content to foster engagement, brand loyalty, and impulse purchases through visual appeal, real-time interactions, and targeted promotions. While intrinsic factors such as convenience and affordability remain central to fast-food consumption, extrinsic influences including social media trends, peer recommendations, and digital campaigns play a significant role in shaping purchasing decisions. Demographic variables, particularly the strong engagement of Millennials and Gen Z with social media content, further highlight the generational differences in responses to marketing strategies. Overall, social media marketing extends beyond short-term sales by building long-term loyalty through brand communities and shaping contemporary consumption patterns.